Examination of environmental knowledge and perceived pro-environmental behavior among students of University Tun Abdul Razak, Malaysia - Ahmad, Siti Nor Bayaah; Juhdi, Nurita; Shaikh Awadz, Azlina (IJAS, 2010)
To promote environmental action among citizens, may be a challenge to any governments that are seeking to reach environmental targets by encouraging individuals to participate in behaviors that will help to reduce negative impact to the environment and the population at large. Such activities include energy saving, waste reduction, energy conservation, recycling and green consumption. However, before such attitude can be transformed into an actual behavior, the citizens’ awareness of environmental problems and knowledge should be strengthened. For that notion, it is the objective of this paper to access the respondents’ knowledge on environmental issues and their perceived pro-environmental behavior. Pearson correlations tests were conducted to examine if there are any associations between the hypothesized relationships (the level of environmental knowledge - perceived pro-environmental behavior; and the attitude towards the environment - perceived pro-environmental behavior). Two hundred and twenty-five respondents participated and they were students of Universiti Tun Abdul Razak which is located at Kelana Jaya, Selangor, Malaysia. This study also sought to determine the level of the students’ level of awareness on environmental related issues, environmental related terminologies and concepts, and the sources of information for environmental knowledge. The results of the study indicated that in general the respondent’s knowledge about the environmental issues was high. However, the respondents were still unfamiliar with certain environmental terms and concepts such as biodegradability and carbon monoxide. It was also found in this study that there is a positive relationship between respondents’ environmental knowledge and their perceived pro-environmentally behavior. Assessing the respondents’ perceived pro environmental behavior through self-assessment method was not enough to bridge the attitude-behavior gap. Therefore, behavior-based environmental attitude scale was included in the study against the respondents’ pro environmental behavior. The findings indicated that out of 6 behavior-based environmental attitude dimensions (energy conservation, mobility and transportation, waste avoidance, recycling, green consumerism and explicit behaviors towards conservation) only 4 that were significantly related to the perceived pro-environmental behavior. Based on the results, analysis on study findings and the implications were made at the last section of the paper.